2020
DOI: 10.3390/md18060333
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Fucoidan against MPP+-Induced SH-SY5Y Cells Apoptosis by Affecting the PI3K/Akt Pathway

Abstract: The main pathologic changes of the Parkinson’s disease (PD) is dopaminergic (DA) neurons lost. Apoptosis was one of the important reasons involved in the DA lost. Our previous study found a fucoidan fraction sulfated heterosaccharide (UF) had neuroprotective activity. The aim of this study was to clarify the mechanism of UF on DA neurons using human dopaminergic neuroblastoma (SH-SY5Y) cells a typical as a PD cellular model. Results showed that UF prevented MPP+-induced SH-SY5Y cells apoptosis and cell death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…inhibitor promoted the activation of the Notch1 signaling pathway, reduced the expression of PTEN and enhanced the activation of Akt, consistent with the study by Zhang et al studies have shown that, following phosphorylation of PI3K and Akt, the target protein Bcl-2 is activated, thereby activating mitochondrial apoptosis. 38,39 These previous findings are consistent with our results. This also partly explains…”
Section: Discussionsupporting
confidence: 93%
“…inhibitor promoted the activation of the Notch1 signaling pathway, reduced the expression of PTEN and enhanced the activation of Akt, consistent with the study by Zhang et al studies have shown that, following phosphorylation of PI3K and Akt, the target protein Bcl-2 is activated, thereby activating mitochondrial apoptosis. 38,39 These previous findings are consistent with our results. This also partly explains…”
Section: Discussionsupporting
confidence: 93%
“…This study aimed to explore the biological function and specific mechanism of OPA in regulating neuron apoptosis in PD. The present results showed that treating SH-SY5Y cells with MPP + prominently reduced cell viability and induced apoptosis, elevated the level of Bax and Caspase3, but decreased the level of Bcl-2, which were in accordance with the previous reports ( Wang and XU, 2005 ; Kim et al, 2016 ; Kim and Park, 2018 ; Liu et al, 2020b ; Liu et al, 2020c ; Yang et al, 2020 ; Zhou et al, 2021 ). However, according to the experimental results of Hoechst 33342 staining and flow cytometry, the apoptosis of SH-SY5Y cells was remarkably inhibited by the pretreatment of OPA in the PD cell model.…”
Section: Discussionsupporting
confidence: 93%
“…Despite increased eEF1A2 levels, PI3K inhibitor-induced cell death was increased. A recent study in MPP + -treated SH-SY5Y cells also found that a PI3K inhibitor LY294002 potentiated apoptosis induced by MPP + , which was accompanied by increased inhibition of phosphorylation of both PI3K and Akt [ 42 ]. Activation of the PI3K/Akt pathway has been shown to inhibit neuronal apoptosis and promote the survival of dopaminergic neurons in a rat model of PD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%